1986
DOI: 10.3109/00207458608985632
|View full text |Cite
|
Sign up to set email alerts
|

Recognition memory and psychophysiological responses to stimuli with neutral or emotional content: A study of korsakoff patients and recently detoxified and longterm abstinent alcoholics

Abstract: Possible relations between chronic alcohol abuse and impairments in cognitive functioning were tested in six groups of subjects, groups A1, A2, CGy, AA, KO, and CGo: The first three groups were about 35 years old, the last three about 50 years. Groups A1 and A2 each consisted of ten men hospitalized for the treatment of alcohol dependency, group A1 having been detoxified for less than one week, and group A2 for more than five months. Group CGy constituted the matched control group. Group AA consisted of six Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 47 publications
1
17
1
Order By: Relevance
“…However, the result of the post hoc analysis indicates that KS participants also did not have a recognition benefit when taking their subjective valence ratings into account. Our results seem to be in contrast to the findings of Markowitsch et al (1986). In their study KS patients' memory performance for pictorial stimuli was enhanced by the emotional content short term.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…However, the result of the post hoc analysis indicates that KS participants also did not have a recognition benefit when taking their subjective valence ratings into account. Our results seem to be in contrast to the findings of Markowitsch et al (1986). In their study KS patients' memory performance for pictorial stimuli was enhanced by the emotional content short term.…”
Section: Discussioncontrasting
confidence: 86%
“…;American Psychiatric Association, 1994) criteria, KS patients' most prominent symptoms are profound anterograde memory disturbances that impair everyday life and, in addition, moderate signs of retrograde amnesia. Memory impairments emerge in different modalities (see Heinrichs, 1994;Holdstock, Mayes, Cezayirli, Aggleton, & Roberts, 1999;Kixmiller, Verfaellie, Mather, & Cermak, 2000) and occur in free recall and in recognition conditions (Kessler, Irle, & Markowitsch, 1986;Kessler, Markowitsch, & Bast-Kessler, 1987;Markowitsch, Kessler, Bast-Kessler, & Riess, 1984;Markowitsch, Kessler, & Denzler, 1986). Remote memory disturbances include a reduced ability to recall autobiographicalepisodic events and semantic knowledge, such as famous events and names (Borsutzky, Fujiwara, & Markowitsch, 2006;Kopelman, Stanhope, & Kingsley, 1999;Mayes, Daum, Markowitsch, & Sauter, 1997).…”
Section: Introductionmentioning
confidence: 96%
“…This result is in accordance with Markowitsch et al (1986) and OscarBerman et al (1990), who found severe emotional processing disturbances in Korsakoff patients. One can argue that judging neutral and negative words as positive may reflect a disinhibition tendency and disturbed control processes: the Korsakoff patients tended to perseverate on judgments of the (initially five) positive words and inferred positive valence also to the other words.…”
Section: Discussionsupporting
confidence: 82%
“…Changes in emotional perception and processing were also noted in few neuropsychological investigations. Though Douglas and Wilkinson (1993) did not find significant deterioration of emotional reactivity in Korsakoff patients, Markowitsch, Kessler, BastKessler, and Riess (1984) and Markowitsch, Kessler, and Denzler (1986) revealed reduced emotional reactivity in their patients. OscarBerman, Hancock, Mildworf, Hutner, and Altman Weber (1990) found affective judgments of Korsakoff patients to be more extreme compared to judgments of controls.…”
Section: Introductionmentioning
confidence: 99%
“…These early studies described the emotional responses of such patients as abnormal. Later studies have found these patients to be sometimes less reactive to emotional stimuli than controls (Markowitsch et al 1986), sometimes more reactive than controls (Oscar-Betman et al 1990), and sometimes normally reactive (Douglas and Wilkenson 1993). The use of different measures and materials to assess reactivity complicates the interpretation of the results.…”
Section: Introductionmentioning
confidence: 99%